Factors Analysis That Shape Solid Gold Jewelry Purchase Decision In East Java - Jennifer (Universitas Ciputra Surabaya, 2022)
Since the COVID-19 pandemic, online sales have become a new habit for all businesses in Indonesia. One of the businesses that experience shifting in sales channels from offline to online is gold jewelry stores. For gold jewelry business players themselves, selling gold online is a new thing and requires uneasy adaptation. Not many studies that specifically discuss consumer behavior towards buying solid gold jewelry online have made researcher want to know what are the factors that shape purchasing decisions. The purpose of this study is to test and analyze whether product quality, design, uniqueness, price, brand, social responsibility, free shipping, coupons and discounts, consumer reviews, returns, quick and easy check out, express delivery, loyalty points, social media, eco-friendly products and interest-free installments shape the decision to buy solid gold jewelry online. The method used is quantitative with a descriptive approach. The data collection process was carried out with the help of a questionnaire and Confirmatory Factor Analysis (CFA) as a data analysis method. The results of this study shows that all variables are statistically significant in shaping the gold purchase decision model. The highest contributing factor is interest-free installments and the lowest contributing factor is design.